STUDIES ON MATURATION ,SPAWINING ,FECUNDITY AND SEX RATIO IN BARBUS (PUNTIUS) SARANA (HAMILTON-BUCHANAN ) FROM LAKE KOLLERU , ANDRA PRADESH. - MURTY, V. SRIRAMACHANDRA (Fishery Technology, 2017)
Barbus sarana contains only one batch of mature ova in the mature ovaries to be spawned in one spawning act. It spawns during July-September. The fecundity ranges from 11,201 to 224,248 ova. There is a positive curvilinear correlation between total length and fecundity, the latter increasing with length at a rate of less than cube of length. The stock of this species from lake KoUeru appears to be more fecund than that inhabiting Loni reservoir. The sex ratio indicates that females outnumber males in all months and in larger length groups. Females appear to reach a larger length than males.